Pengaruh Kebiasaan Menonton Tayangan My Trip My Adventure terhadap Kemampuan Menulis Pengalaman Pribadi oleh Siswa SD Tarbiyah Islamiyah Hamparan Perak - Amnur Rifai Dewirsyah (Medan Resource Center, 2023)
This article aims to determine the influence of the habit of watching My Trip My Adventure on students' ability to write personal experiences at SD Tarbiyah Islamiyah Hamparan Perak in the 2016–2017 academic year. The population of this study were all students of SD Tarbiyah Islamiyah Hamparan Perak consisting of two classes with a total of 76 people. The results of the ability to write personal experiences without the habit of watching My Trip My Adventure shows for students of Tarbiyah Islamiyah Hamparan Perak Elementary School, namely 2.6% (1 person) got the very good category, 57% (22 people) got the good category. enough category, and 22% (8 people) got the enough category, and 18.4% (7 people) were in the less category. The results of the ability to write personal experiences with the habit of watching My Trip My Adventure shows students of SD Tarbiyah Islamiyah Hamparan Perak have an assessment proportion of 13.2% (5 people) getting very good category, 39.5% (15 people) good category, 21.1% (8 people) moderate category, 21.1% (8 people) less category, and 5.26% (2 people) very less category. Based on the results of the hypothesis test, it shows that there is an influence from the habit of watching My Trip My Adventure on the ability to write personal experiences of SD Tarbiyah Islamiyah Hamparan Perak students. After obtaining the tcount value, then it is compared with ttable at a significant level ? = 0.05% with dk = N1 + N2 – 2 = 74. Based on the calculation results obtained ttable = 1.992. Thus, it can be seen that tcount>table is 8.357 > 1.992.